UTILIZATION OF ETHYL ACETATE FRACTION KETAPANG LEAF (Terminalia catappa) AS BIOREDUCTOR IN SYNTHESIS GOLD NANOPARTICLES AND ANALYSIS ANTIBACTERIAL PROPERTIES - Sarwina Hafid; Muhammad Zakir; Seniwati Dali (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
Gold nanoparticles was synthesized by bioreduction method using ethyl acetate fraction of ketapang leaf (Terminalia catappa). Nanoparticles formed were characterized using spectrophotometer UV-Vis, Fourier Transform Infra Red (FTIR) and X-Ray Diffraction (XRD). In the   analysis   of   spectrophotometer   UV-Vis   gold   nanoparticles   with   a   precursor   solution concentration of 0.5 mM and 1 mM each has an absorption between 533.5-540 nm and 539-587 nm. Analysis of functional groups of gold nanoparticles was analyzed by Fourier Transform Infra Red (FTIR). Crystal system of gold nanoparticles is cubic with nanoparticles size of 17.13 nm. The evaluation of test antibacterial activity was performed using several bacteria test such as Staphylococcus aureus, Escherichia coli, and Bacillus subtilis. Gold nanoparticles can not inhibit the activity of a test bacterium Staphylococcus aureus, Escherichia coli, and Bacillus subtilis so that differences in the concentration of gold nanoparticles did not affect the inhibition of bacteria.